Electrochemical investigation of metal-free and nickel-containing porphyrazines carrying eight tosylaminoethylthia groups - KOCA, ATIF (SPRINGER WIEN, 2002)
In this study, the electrochemical properties of metal-free and nickel-containing porphyrazines with eight tosylaminoethylthia groups were investigated using cyclic voltammetry, double potential step chronoamperometry, double potential step chronocoulometry, and controlled potential coulometry. Cyclic voltammetry measurements showed that both compounds exhibit two quasi-reversible and an irreversible reduction waves. The first electron transfer reaction was followed by an irreversible chemical reaction, the second one by a reversible chemical reaction for both species. The electrode processes of metal-free and nickel-containing porphyrazines are diffusion controlled, but the double potential step chronocoulometry measurements indicated that the nickel porphyrazine is adsorbed at the electrode. However, a small adsorption current has no significant effect on the mass transport mechanism of the system. Diffusion coefficients of both compounds were determined by both cyclic voltammetric and chronocoulometric measurements. The diffusion coefficients of the reduced forms of the porphyrazines were found to be smaller than those of the neutral forms.
Keywords: cyclic voltammetry; electrochemistry; nickel; porphyrazines; PHTHALOCYANINES; ADSORPTION; COMPLEXES; CHEMISTRY; CARBON